Optimal design of anti‐interrupted sampling repeater jamming waveform for missile‐borne radar based on an improved genetic algorithm - Fei Cao (Wiley, 2021)
Abstract The optimal design of transmitted waveforms to improve the performance of missile‐borne radar in suppressing interrupted sampling repeater jamming (ISRJ) is studied here. The waveform diversity property requires that the waveform group has excellent orthogonality (good auto‐ and cross‐correlation properties), which is an effective waveform optimisation design method for missile‐borne radar electronic counter‐countermeasures. The principle of orthogonal phase coding waveform against ISRJ is studied and the use of chaotic sequences is proposed to initialise the population, as well as a simulated annealing selection operator, which improves the convergence speed of the improved genetic algorithm (IGA) and enhances the global optimisation ability. The IGA improves the shortcomings of GA, that is, easily falling into a local optimum and slow search speed, and can realise a global search for longer orthogonal polyphase coding sequence sets. The simulation examples demonstrate the good jamming suppression performance of the proposed method.